Bilayered composite restoration: the effect of layer thickness on fracture behavior. Issue 1 (1st January 2020) - Lassila, Lippo; Säilynoja, Eija; Prinssi, Roosa; Vallittu, Pekka K.; Garoushi, Sufyan
Abstract: Purpose: By combining the increased toughness of a resin composite reinforced with discontinuous fibers and the surface wear resistance of a particulate filler composite (PFC), a bilayered composite technique was recently introduced. This study aimed to evaluate the effect of the thickness of the overlaying PFC placed over a fiber-reinforced composite (FRC) core, on the fracture-behavior of direct crown restorations. Methods: Six groups of posterior crown restorations ( n = 8/group) were fabricated having a discontinuous FRC-core (everX Flow) and a layer of surface PFC (Essentia U) with various thicknesses (0.5, 1.0, 1.5, 2.0 mm), with the remaining thickness of the bilayered being 6 mm. Control groups were only made of PFC or FRC materials. Restorations were statically loaded until fracture. Failure-modes were visually examined. Data were analyzed using ANOVA ( p = .05) and regression analysis. Results: The regression analysis showed that by decreasing the thickness of PFC layer, the load bearing capacity of restorations increased linearly (R 2 =0.7909). ANOVA revealed that crown restorations made only from everX Flow composite had significantly higher load-bearing capacities (3990 ± 331 N) ( p < .05) among all the groups tested. With regard to the failure-mode analysis, crowns that had a FRC core material of everX Flow revealed delamination of the PFC surface composite from the core. Crowns which were made only of PFC i.e. with no fiber reinforcement, showed a crushing-like fracture pattern. Conclusions: Restorations combining a thick FRC-core and a thin surface layer of PFC (0.5–1 mm), displayed promising performance related to fracture-behavior and load-bearing capacity.